Penerapan Media Pembelajaran Videoscribe pada Materi Sistem Reproduksi Manusia Kelas XI - Daeli, Dirikan Hati; Gea, Yana Arnila; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this study is to explore the results of the application of videoscribe media in the context of learning the human reproductive system. The method in this article uses a qualitative approach with a literature study method. The main purpose of the search is to obtain a theoretical basis and a framework of thinking. The main source of data for this research is scientific articles published in various scientific journals and indexed on the google scholar database. Data analysis that qualitative data analysis consists of data reduction, data presentation, and conclusion drawing. The results of this study confirm that the application of videoscribe media in the learning process has very meaningful benefits. This media can increase student motivation and engagement, which ultimately results in a deeper understanding of the material. This has an impact on a significant increase in student learning outcomes. In addition, the use of videoscribe provides an opportunity for teachers to better understand the effectiveness and efficiency of these media in learning, so that they can better adjust teaching strategies to achieve optimal student learning outcomes. Practically, the use of videoscribe media stimulates students' motivation and participation in learning, as well as increases their involvement in understanding the subject matter